SÚWRETLEW KÓRKEM ÓNERI QURALLARÍ ARQALÍ STUDENTLERDI ESTETIKALÍQ RAWAJLANDÍRÍW TIYKARLARÍ - Urazimova, Tamara Valerevna (SCIENCE and SOCIETY, 2026)
The article reveals the features of the foundations of students' aesthetic development through the means of fine arts. The aesthetic development of students using fine arts means is based on forming the ability to perceive and understand beauty, developing aesthetic taste and creative abilities through familiarization with works of art and independent creative activity. To achieve this goal, various methods are used, such as viewing and analyzing works of painting, sculpture, and graphics, studying their history and influence, as well as practical classes in drawing and other types of creativity.